An - Kegan, Robert (Harvard Business Review Press, 2016)
An Everyone Culture dives deep into the worlds of three leading companies that embody this breakthrough approach. It reveals the design principles, concrete practices, and underlying science at the heart of DDOs—from their disciplined approach to giving feedback, to how they use meetings, to the distinctive way that managers and leaders define their roles. The authors then show readers how to build this developmental culture in their own organizations